Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Pegawai Pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Jambi - Arman Syafa’at; Andri Devita (J-MAS (Jurnal Manajemen dan Sains), 2021)
The research entitled Effect Of The Work Environment And Work Load On Employee Performance In The Jambi Provincial Regional Financial And Assets Management Agency uses primary data which is presented in the form of a sample size for employees at the Regional Financial and Asset Management Agency of Jambi Province, namely Civil Servants who are 108 employees while the sample for honorary employees is 21 employees, so the total sample of employees is 129 people. The results showed that 1). Work Environment Variable (X1) Respondents' answers to the work environment variable averaged 3.65 or 73.01% with the criteria for a good work environment. Thus, it can be stated that "There is a significant influence between the work environment on employee performance at BPKAD Jambi Province". 2). Workload Variable (X2) Respondents' answers to the workload variable average 3.65 or 73.01% with the criteria of the workload is good or according to the distribution. Thus, it can be stated that: "There is a significant influence between workload and employee performance at BPKAD Jambi Province", it can be accepted the truth. 3). Effect of Variables X1 and X2 on Variable Y The results of the calculation F = 13,758 with (Sig) 0.000 <0.05, which means that Ho is rejected and Ha is accepted. There is a significant influence of work environment and workload on employee performance at BPKAD Jambi Province. With an R square value of 0.756, which means that together the work environment and workload variables influence the low (depending on the value variation) of the employee performance variables at BPKAD Jambi Province by 75.60%.